2004
DOI: 10.1186/1471-2334-4-32
|View full text |Cite
|
Sign up to set email alerts
|

Mutational dynamics of the SARS coronavirus in cell culture and human populations isolated in 2003

Abstract: Background: The SARS coronavirus is the etiologic agent for the epidemic of the Severe Acute Respiratory Syndrome. The recent emergence of this new pathogen, the careful tracing of its transmission patterns, and the ability to propagate in culture allows the exploration of the mutational dynamics of the SARS-CoV in human populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 14 publications
3
61
0
Order By: Relevance
“…Effective inactivation was demonstrated against two independent viral isolates. The phylogenetic analysis showed that the two strains employed in this study have a common origin being more similar to those that originated in Hong Kong than those in North China and Taiwan (Vega et al ., 2004; Vicenzi et al ., 2004). By nucleotide sequence comparison, the Urbani isolate only differs by six nucleotide changes from the HSR1 isolate (Rota et al ., 2003; Ruan et al ., 2003; Vicenzi et al ., 2004).…”
Section: Discussionmentioning
confidence: 85%
“…Effective inactivation was demonstrated against two independent viral isolates. The phylogenetic analysis showed that the two strains employed in this study have a common origin being more similar to those that originated in Hong Kong than those in North China and Taiwan (Vega et al ., 2004; Vicenzi et al ., 2004). By nucleotide sequence comparison, the Urbani isolate only differs by six nucleotide changes from the HSR1 isolate (Rota et al ., 2003; Ruan et al ., 2003; Vicenzi et al ., 2004).…”
Section: Discussionmentioning
confidence: 85%
“…Zhao et al (2004) analyzed 11 genomic sequences from different parts of the world during 2003 SARS epidemic and found that the mutation rate to be in the order of 0.80-2.38 × 10 −3 nucleotide substitution per site per year (2.2-6.7 × 10 −6 nucleotide substitutions per site per day) and the most recent common ancestor of the sequences was inferred to be present as early as the spring of 2002. Analysis on the Singapore isolates from the 2003 epidemic revealed that the mutation rate to be 5.7 × 10 −6 nucleotide substitutions per site per day, with the rates for synonymous and non-synonymous mutations at 2.5 × 10 −6 and 3.2 × 10 −6 nucleotide substitutions per site per day, respectively (Vega et al, 2004). All the above studies used human samples with available clinical data from the 2003 outbreak and the substitution rates of SARS-CoV genome obtained from the various studies were in good agreement with each other.…”
Section: Evolutionary Perspectivesmentioning
confidence: 99%
“…However, more recent reports indicate that SARS-CoV is distinct from the civet virus and it has not been answered so far whether the SARS-CoV originated from civet, or civet was infected from other species 9., 10.. The genome is relatively stable, since its mutation rate has been determined to be between 1.83×10 −6 and 8.26×10 −6 nucleotide substitutions per site per day (11) .…”
Section: Introductionmentioning
confidence: 99%